Promising Indicators in Probiotic-recommendations in COVID-19 and its Accompanying Diseases - Tsaturyan, Vardan; Kushugulova, Almagul; Mirzabekyan, Susanna; Sidamonidze, Ketevan; Tsereteli, David; Torok, Tamas; Pepoyan, Astghik (Open Access Macedonian Journal of Medical Sciences, 2022)
Scientific data suggests the possible beneficial role of probiotics in treatments for COVID-19, but the species/strains-specificity and disease-specificity of probiotics need high attention in choosing the appropriate probiotic in diseases, in particularly in the COVID-19. We hope this review will raise awareness of the COVID-19 probiotic recommendations, highlighting the latest scientific information about virus/hydrogen peroxide/probiotics and the importance of finding out of a specific “criterion” for the probiotics’ recommendation in this disease.